1995
DOI: 10.1002/gps.930101111
|View full text |Cite
|
Sign up to set email alerts
|

Delusional depression in elderly patients: Characteristics and relationship to age at onset

Abstract: SUMMARYIn a prospective study, 34 patients with delusional depression were compared with 100 non-psychotically depressed patients and a subgroup of 30 age-and sex-matched control patients. Depressed patients with delusions were more likely to be single, especially single men. The most common delusions were those of persecution and hypochondriasis. There were no striking differences in other depression symptoms and no evidence for the hypothesis that delusional depression is associated with a later age of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 20 publications
2
31
2
Order By: Relevance
“…Our ®ndings were in line with those of other geriatric studies (Baldwin, 1995;Kivela and Pahkala, 1989). George (1994) suggested that unmarried, divorced, separated, or widowed subjects in old age are at greater risk for developing depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our ®ndings were in line with those of other geriatric studies (Baldwin, 1995;Kivela and Pahkala, 1989). George (1994) suggested that unmarried, divorced, separated, or widowed subjects in old age are at greater risk for developing depression.…”
Section: Discussionsupporting
confidence: 93%
“…In geriatric inpatient studies, Meyers and Greenberg (1986) presented results very similar to ours claiming that an age effect occurring only after the seventh decade of life could be washed out in studies using mixed-age samples with mean ages usually under 60 years. Nelson et al (1989), in a retrospective study, and Baldwin (1995) in a prospective study, also using geriatric samples, did not ®nd any differences as regards age at onset between PMD and NPMD patients. Elderly depressives may have a greater vulnerability in developing PMD, due to their abnormalities of cortisol (Alexopoulos et al, 1984;Davis et al, 1984;Stokes et al, 1984;Greden et al, 1986) and dopamine regulation (Schatzberg et al, 1984(Schatzberg et al, , 1995Meyers et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…To this time, the investigation of delusions in depressive disorders focused, almost exclusively, on the types of their thematic content, neglecting thus other more formal features [10][11][12][13][14]. The present study aims at contributing to the solution of the aforementioned differential diagnostic problem by focusing on more formal features of delusional beliefs, as well as on broader dimensions thereof, obtained through the application of multivariate statistical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the investigators of delusions of PMD in the elderly have mainly adopted a categorical approach to their study (Meyers and Greenberg, 1986;Baldwin, 1995;Gournellis et al, 2001). The only available dimensional study of PMD included patients of all ageranges (Meyers et al, 2006).…”
Section: Introductionmentioning
confidence: 99%